2009
DOI: 10.1007/978-3-642-10865-5_15
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Vivaldi: Achieving Increased Accuracy and Stability

Abstract: Abstract. Network Coordinates are a basic building block for most peer-to-peer applications nowadays. They optimize the peer selection process by allowing the nodes to preferably attach to peers to whom they then experience a low round trip time. Albeit there has been substantial research effort in this topic over the last years, the optimization of the various network coordinate algorithms has not been pursued systematically yet. Analyzing the well-known Vivaldi algorithm and its proposed optimizations with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In [3] we showed that one can achieve very good results with this algorithm, depending on the chosen parameters. However, both algorithms are far from producing optimal results.…”
Section: The Vivaldi Algorithmmentioning
confidence: 93%
See 1 more Smart Citation
“…In [3] we showed that one can achieve very good results with this algorithm, depending on the chosen parameters. However, both algorithms are far from producing optimal results.…”
Section: The Vivaldi Algorithmmentioning
confidence: 93%
“…Furthermore, two additional data sets were used in our complete study in [7]. We used optimal parameters for both algorithms, derived from previous work [3]. We used a 4D space for R 0 , and a 2D space for R i with i > 0.…”
Section: Data Sets and Simulatormentioning
confidence: 99%
“…First, we analyzed the structural correctness of the overlay. We used input data from the RocketFuel [37] project to create a realistic copy of the Nacamar/Tiscali provider network. Furthermore, the same code ran on PlanetLab using 118 nodes.…”
Section: Simulationmentioning
confidence: 99%
“…This is done by getCandidates (Line 4) which only selects valid nodes of the two-hop neighborhood 7 of the given v base -node which is the starting point for each anchor search iteration. Following Song's approach, we choose a node minimizing the 7 Two hops are needed because of the alternating directions on the anchor tree relative prediction error e p (Lines 5-11), as defined in Equation 5. When no anchor can be found for a given base node because of non-available measurements, we choose another base node as a fallback.…”
Section: Fig 3: Embedding Visualizationmentioning
confidence: 99%
“…Vivaldi's performance has been further improved by Elser at al. [7]. Common to these approaches is that the accuracy is highly susceptible to triangle inequality violations (TIVs).…”
Section: Related Workmentioning
confidence: 99%